Identification of miRNAs Involved in Stolon Formation in Tulipa edulis by High-Throughput Sequencing - Zhu, Zaibiao; Miao, Yuanyuan; Guo, Qiaosheng; Zhu, Yunhao; Yang, Xiaohua; Sun, Yuan (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs) are a class of endogenous, non-coding small RNAs that play an important role in transcriptional and post-transcriptional gene regulation. However, the sequence information and functions of miRNAs are still unexplored in Tulipa edulis. In this study, high-throughput sequencing was used to identify small RNAs in stolon formation stages (stage 1, stage 2, and stage 3) in T. edulis. A total of 12,890,912, 12,182,122, and 12,061,434 clean reads were obtained from stage 1, stage 2, and stage 3, respectively. Among the reads, 88 conserved miRNAs and 70 novel miRNAs were identified. Target prediction of 122 miRNAs resulted in 531 potential target genes. Nr, Swiss-Prot, GO, COG and KEGG annotations revealed that these target genes participate in many biologic and metabolic processes. Moreover, qRT-PCR was performed to analyze the expression levels of the miRNAs and target genes in stolon formation. The results revealed that miRNAs play a key role in T. edulis stolon formation.